Device Simulation of Ag2SrSnS4 and Ag2SrSnSe4 Based Thin‐Film Solar Cells from Scratch. Issue 2 (23rd November 2021) - Srivastava, Ashutosh; Tripathy, Susanta Kumar; Lenka, Trupti Ranjan; Hvizdos, Pavol; Menon, P. Susthitha; Lin, Fen; Aberle, Armin Gerhard
Abstract: The structural, optoelectronic and elastic properties of quaternary chalcogenide materials Ag2 SrSn(S/Se)4 in kesterite (Kes) and stannite (Sta) phases are studied using the HSE hybrid functional within the density functional theory. Ag2 SrSnSe4 in kesterite and stannite phases is found to have direct bandgap of 1.13 and 1.38 eV, respectively, along the high symmetry Γ points. To analyze the electronic properties, PDOS for Ag2 SrSn(S/Se)4 in kesterite and stannite phases are studied and explained. To get more insights into the optical behavior of the materials the authors also investigate the dielectric function, refractive function, absorption spectrum, extinction coefficient, reflectivity, and optical conductivity. They also calculate the single‐layer absorber efficiency of Ag2 SrSn(S/Se)4 in kesterite and stannite phases using the spectroscopic limited maximum efficiency (SLME) approach to predict their potential as an efficient absorber layer material in thin‐film solar cells (TFSC). The SLME for Ag2 SrSnSe4 in kesterite and stannite phases is found to be 31.4% and 32.4%, respectively. Further, a complete solar cell device analysis with these materials as an absorber layer is carried out using the SCAPS‐1D software. They found that devices with the kesterite and stannite structure of Ag2 SrSnSe4 have a predicted efficiency of 20.04% and 18.59%, respectively. Abstract : Novel Ag2 SrSn(S/Se)4 materials in its kesterite and stannite phases has been studied for the first time. Optical properties of Ag2 SrSnSe4 are found to be better than Ag2 SrSnS4 . Ag2 SrSnSe4 (Kes) with 1.13 eV bandgap has excellent SLME of 31.4%. Ag2 SrSnSe4 (Kes) and Ag2 SrSnSe4 (Sta) based devices have a PCE of 20.04% and 18.59%, respectively.